2011
DOI: 10.1080/09603107.2011.581210
|View full text |Cite
|
Sign up to set email alerts
|

The empirical relationship between home equity borrowing and durable goods purchases

Abstract: The current financial crisis has drawn attention to consumers' use of the Home Equity Line of Credit (HELOC) to finance consumption. Although many economists have repeatedly noted that such borrowing fueled additional consumption, attempts to quantify the boost to consumer spending have been relatively few. Similarly, attempts to classify the types of goods consumers purchased with their HELOC facilities have been sparse. The present article remedies both situations. The article shows that, in the aggregate, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It has been found that home equity lines of credit are not used for appliance purchases by baby boomers in the high-income segment as incomes grow [43]. In addition, the presence of working wives has not resulted in the wives in a significant increase in expenditure on appliances, though it did have a positive impact on family income [44].…”
Section: Expenditure On Furniture and Appliancesmentioning
confidence: 99%
“…It has been found that home equity lines of credit are not used for appliance purchases by baby boomers in the high-income segment as incomes grow [43]. In addition, the presence of working wives has not resulted in the wives in a significant increase in expenditure on appliances, though it did have a positive impact on family income [44].…”
Section: Expenditure On Furniture and Appliancesmentioning
confidence: 99%